Comparison of Three-Bag Method Acetylcysteine Versus Two-Bag Method Acetylcysteine for the Treatment of Acetaminophen Toxicity: An Updated Systematic Review and Meta-Analysis - Mohammed Alrashed; Abdulrahman Alyousef; Hisham A. Badreldin; Khalid Bin Saleh; Shmeylan Al Harbi; Abdulkareem M. Albekairy; Abrar Alghamdi; Amal Al-Nahdi; Dhay Alonazi; Mohammed Alnuhait; Abdullah Alshammari; Tariq Alqahtani (Diseases)
Background: Acetaminophen is generally considered safe when used according to the recommended guidelines. Consumption in excessive doses can lead to severe liver damage and, in critical cases, may even result in death. To reduce the effects of acetaminophen overdose, N-acetylcysteine (NAC) has been established as the preferred intervention to prevent liver damage. Objectives: The purpose of this updated systematic review and meta-analysis is to evaluate the potential benefits of a two-bag N-acetylcysteine (NAC) dosing regimen compared to the traditional three-bag protocol in the treatment of acetaminophen-induced liver toxicity. Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The research team utilized the PubMed and Cochrane databases to perform a thorough and comprehensive search of the relevant literature from the inception of these databases up until January 2024. Results: Nine studies were included. The overall use of two-bag NAC was associated with lower anaphylactic reactions and gastrointestinal symptoms compared to the three-bag method. The rate of liver toxicity resolution was the same between the two treatment groups. Conclusions: The two-bag NAC regimen can be considered a safe and effective method for managing acetaminophen toxicity.